Task-Based Development of Interpretative Reading Materials in an English Language Education Context - Yunus, Muhammad; Rahmawati, Sitti; Bachtiar, Nurhalizah; Afdhalia, Vira (Tamaddun Life, 2025)
Interpretative reading ability is a crucial skill in English language education, as it requires students not only to comprehend literal meanings but also to critically interpret and evaluate information. However, instructional practices in higher education remain dominated by conventional, decontextualized teaching materials, which insufficiently support the development of higher-order thinking skills. This study aimed to (1) identify students’ needs regarding interpretative reading materials and (2) design and develop task-based instructional materials to enhance interpretative reading ability. The study employed a Research and Development (R&D) method using the Borg & Gall model, encompassing needs analysis, design, development, expert validation, revision, and limited field testing. Data were collected through needs questionnaires, interviews, and expert judgments, and were analyzed using descriptive qualitative and quantitative techniques. The findings indicate that students require more contextualized and interactive interpretative reading materials equipped with explicit strategies to help them overcome difficulties in understanding implicit meanings, making inferences, and analyzing text structure. Questionnaire data reveal that most students need a variety of authentic tasks, step-by-step reading guidance, task completion models, and collaborative activities to enhance engagement and interpretative comprehension. Based on these findings, task-based materials were successfully designed by integrating pre-task, task-cycle, and post-task stages, complemented by interpretative strategy exercises, analytical tasks, group collaboration, and formative evaluation in each unit. This design is considered responsive to students’ needs and has the potential to effectively improve interpretative reading ability in English language learning contexts at the tertiary level.